2003
DOI: 10.2224/sbp.2003.31.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Differences in Decision-Making Styles: A Study of College Students in Five Countries

Abstract: The major goal of this study was to explore cultural differences in decision-making styles of college students from 5 countries: Korea, Japan, China, the United States, and Canada. On the basis of previous scholarly findings, a questionnaire was developed and distributed to 837 college students in the 5 countries. Of these, 815 were included in the statistical analysis. 2 hypotheses were established that examine 5 decision-making styles: cooperative, collaborative, avoidant, competitive, and dominant. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Thereby, it is valuable to study EVs adoption status and consumers purchasing behavior on EVs in Shenzhen. However, previous scholarly findings shows that there are dramatically differences exist in decision-making and value orientation between Western people and Chinese [12], some other research findings indicates that Netherlands consumers pay high attention to value and safety [13], the French favor design, style and fashion in car advertisement [13], German and Italian consumers have similar characteristic with French, they prefer fast, advanced technology and stylish and multi-function cars [13]. In contrast, American consumers consider cars as a symbol of status and pursue big and powerful vehicles [13].…”
Section: Introductionmentioning
confidence: 95%
“…Thereby, it is valuable to study EVs adoption status and consumers purchasing behavior on EVs in Shenzhen. However, previous scholarly findings shows that there are dramatically differences exist in decision-making and value orientation between Western people and Chinese [12], some other research findings indicates that Netherlands consumers pay high attention to value and safety [13], the French favor design, style and fashion in car advertisement [13], German and Italian consumers have similar characteristic with French, they prefer fast, advanced technology and stylish and multi-function cars [13]. In contrast, American consumers consider cars as a symbol of status and pursue big and powerful vehicles [13].…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, these associations are compatible with the results of Gadassi et al (2012), who found that these dimensions of the CDMP were associated with fewer emotional and personality-related career decision-making difficulties. (Yi & Park, 2003), where one tends to forgo one's own goals for the sake of the goals of the group, and see one's own fate as intertwined with that of the group (Triandis, 1990).…”
Section: Cross-cultural Analysis Of Career Decision Making 20mentioning
confidence: 99%
“…Kim, Wang, Kondo, and Kim (2007) looked at conflict management styles of corporate subordinates and supervisors and found that Japanese use obliging styles more than Chinese and Koreans, whereas Koreans use compromising styles more than Chinese and Japanese. Yi and Park (2003) observed decision-making styles within interpersonal conflict among Americans, Canadians, Chinese, Japanese, and Koreans in their questionnaire survey and discovered that Koreans preferred dominating and obliging styles, whereas Japanese scored low on all styles relative to the other cultures. Judging from these findings, it would appear that Chinese, Japanese, and Koreans are likely to prefer different conflict management styles.…”
Section: Cultural Difference In Conflict Management Strategies In Chimentioning
confidence: 99%